Associations of burnout with job demands/resources during the pandemic in health workers from Southeast European countries - Dragan Mijakoski; Aneta Atanasovska; Dragana Bislimovska; Hana Brborović; Ognjen Brborović; Ljiljana Cvjeanov Kezunović; Milan Milošević; Jordan Minov; Buhara Önal; Nurka Pranjić; Liliana Rapas; Sasho Stoleski; et al. (Frontiers in Psychology, 2023)
IntroductionDespite several studies assessing job demands and burnout in countries from the Southeast European (SEE) region, there is still a lack of data about the psychological impact of the pandemic on health workers (HWs).AimsThe present study aimed to demonstrate and compare levels of burnout dimensions in HWs from SEE countries and to reveal the burnout–job demands/resources relationships in these workers during the pandemic.Materials and methodsDuring the autumn of 2020, this online multicentric cross-sectional survey studied a large group (N = 4.621) of HWs working in SEE countries. The Maslach Burnout Inventory was used for the measurement of burnout dimensions. We analyzed the job demands by using the Hospital Experience Scale. Remuneration and relationships with superiors were measured using the Questionnaire sur les Ressources et Contraintes Professionnelles (English version).ResultsA series of ANOVA comparisons of means revealed the countries in which respondents showed higher mean values of emotional exhaustion (Bosnia and Herzegovina, Bulgaria, Croatia, Moldova, Montenegro, and North Macedonia) and the countries in which respondents showed lower mean values of this burnout dimension (Israel and Romania) (Welch F = 17.98, p < 0.001). We also found differences among HWs from different countries in job demands and job resources. The testing of hierarchical regression models, which have been controlled for certain confounding factors, clearly revealed that emotional exhaustion was predicted by job demands (R2 = 0.37) and job resources (R2 = 0.16).ConclusionPreventive measures for the improvement of mental health in HWs during the pandemic and beyond have to take into account the differences between countries regarding the country context and current scientific knowledge. A modified stress test should be implemented in hospitals regarding future shocks that might include new pandemics, terrorism, catastrophes, or border conflicts.